Paroxysmal exercise induced dyskinesia and writer’s cramps in twin siblings with SLC2A1 mutation - Banotra, Pankaj; Bharti, Anamika; Wangnoo, Areca (International Journal of Research in Medical Sciences, 2022)
Paroxysmal exercise induced dyskinesias (PED) are rare disorders with recurring episodes of sudden involuntary movement disorders precipitated by physical exercise. It had been reported that less than 20% of PED patients carry an SLC2A1 mutation encoding GLUT 1 of whom 49 patients have been identified worldwide We hereby reported a case of twin siblings, 23 year old male with no antecedent other past illness and family history presenting with writer’s cramps and paroxysmal exercise induced dyskinesia attributed to milder phenotype of glucose transporter type 1 deficiency with the heterozygous exon-6 SLC2A1 gene mutation. Ketogenic diet in these patients may help in these cases.